Simultaneous Presentation of Follicular Lymphoma and Diffuse Large B-cell lymphoma (DLBCL): A Case Report - Handayani, Rosmeri; Kosasih, Agus Susanto (Indonesian Journal of Cancer, 2025)
Introduction: The natural history of follicular lymphoma (FL) is frequently characterized by transformation to a more aggressive diffuse large B-cell lymphoma (DLBCL). Outcomes of patients with histologic transformation (HT) of FL have been believed to be poor. However, a leucocytosis at presentation is infrequently described. In this report, we present a case of simultaneous presentation of follicular lymphoma and DLBCL.Case Presentation: A 50-year-old male patient presented to a head and neck specialist with complaints of slowly progressing swelling in the nose on the left side for a duration of 1 year, diagnosed with nasofarynx carcinoma. After excision surgery, the patient was referred to an internist for follow-up on the leukocytosis. Biopsy and immunohistochemistry from the nose and tonsil were suggestive of DLBCL. However, bone marrow aspiration was suggestive of follicular lymphoma. After a complete work-up, he was diagnosed with DLBCL and was treated with six cycles of the standard (CHOP) regimen. The patient’s history revealed a leukocytosis for 4 years prior to cardiac catheterization.Conclusion: These findings suggest a clonal relationship between the two types of lymphoma cells. Furthermore, they support the transformation of an acute follicular lymphoma into a composite lymphoma combining a high-grade B-cell lymphoma. Understanding the natural history of follicular lymphoma can aid the diagnosis and implies a worse prognosis in patients compared to de novo DLBCL.